2009
DOI: 10.1152/jn.91174.2008
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Potassium Homeostasis Underlies Hyperthermic Conduction Failure in Control and Preconditioned Locusts

Abstract: At extreme temperature, neurons cease to function appropriately. Prior exposure to a heat stress (heat shock [HS]) can extend the temperature range for action potential conduction in the axon, but how this occurs is not well understood. Here we use electrophysiological recordings from the axon of a locust visual interneuron, the descending contralateral movement detector (DCMD), to examine what physiological changes result in conduction failure and what modifications allow for the observed plasticity following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…This raises the question of why these insects, and potentially animals in general, adapted to destabilize cellular homeostasis in response to anoxic stress. It is worth noting that this physiological response to anoxia similarly occurs in insects exposed to hypothermic and hyperthermic stress [92,93,102]. When examining the common links between these stressors in insects and in the anoxic turtle brain, it is clear that a key factor is maintaining the balance between ATP supply and demand [9], as the Na + /K + ATPase in the human nervous system consumes approximately two-thirds of all ATP produced [103].…”
Section: Neuronal Depression As a Mechanism Of Anoxic Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises the question of why these insects, and potentially animals in general, adapted to destabilize cellular homeostasis in response to anoxic stress. It is worth noting that this physiological response to anoxia similarly occurs in insects exposed to hypothermic and hyperthermic stress [92,93,102]. When examining the common links between these stressors in insects and in the anoxic turtle brain, it is clear that a key factor is maintaining the balance between ATP supply and demand [9], as the Na + /K + ATPase in the human nervous system consumes approximately two-thirds of all ATP produced [103].…”
Section: Neuronal Depression As a Mechanism Of Anoxic Survivalmentioning
confidence: 99%
“…Heat shock (HS) is one such stressor that results in the PC phenotype, although the neurophysiological consequences resulting from the upregulation of HSPs are unclear. One mechanism that has been described occurs in neurons of the insect Locusta migratoria , where a prior HS of 45°C for 3 h and a 1-h recovery leads to the transcription and translation of a number of HSPs with a concomitant reduction in whole-cell K + conductance in the brain [102,104]. The whole-cell peak current (A current) of the K + channels is not disturbed, while the prolonged transient current (B current) is significantly reduced [105].…”
Section: Neuronal Depression As a Mechanism Of Anoxic Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct differences in neural thermal tolerance can be explained by changes in enzyme isoform and membrane restructuring but can also result from changes in neural K ϩ conductance (a hypothesis that is based upon previous work in insect models; Wu et al 2001;Robertson 2004aRobertson , 2004bMoney et al 2009). For insects, it has been demonstrated that increasing temperature in Locusta migratoria increases the K ϩ conductance of neurons, resulting in nerve transmission failures; that similar failures can be induced by adding K ϩ to the extracellular fluid (simulating increased K ϩ conductance; Money et al 2009); and that such failures can be prevented by pharmacologically blocking K ϩ channels (Wu et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For insects, it has been demonstrated that increasing temperature in Locusta migratoria increases the K ϩ conductance of neurons, resulting in nerve transmission failures; that similar failures can be induced by adding K ϩ to the extracellular fluid (simulating increased K ϩ conductance; Money et al 2009); and that such failures can be prevented by pharmacologically blocking K ϩ channels (Wu et al 2001). Additionally, increased survival after sublethal heat stress has also been associated with a decrease in nerve membrane K ϩ conductance (Ramirez et al 1999;Money et al 2009). Differences in K ϩ conductance have been shown to correlate with a species' habitat temperature (Rosenthal and Bezanilla 2002).…”
Section: Discussionmentioning
confidence: 99%